2018
DOI: 10.1088/1478-3975/aab6d6
|View full text |Cite
|
Sign up to set email alerts
|

The physicist’s guide to one of biotechnology’s hottest new topics: CRISPR-Cas

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated proteins (Cas) constitute a multi-functional, constantly evolving immune system in bacteria and archaea cells. A heritable, molecular memory is generated of phage, plasmids, or other mobile genetic elements that attempt to attack the cell. This memory is used to recognize and interfere with subsequent invasions from the same genetic elements. This versatile prokaryotic tool has also been used to advance applications in bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 227 publications
(458 reference statements)
1
19
0
Order By: Relevance
“…The CRISPR-Cas mechanism for immunity has three stages [2,3]. Following a first encounter with a virus, after a successful defense through another mechanism or if the virus is ineffective for some reason [4], some of the Cas proteins recruit pieces of viral DNA and integrate these "spacers" into an array separated by palindromic repeated sequences in the CRIPSR locus of the bacte-rial genome.…”
Section: Introductionmentioning
confidence: 99%
“…The CRISPR-Cas mechanism for immunity has three stages [2,3]. Following a first encounter with a virus, after a successful defense through another mechanism or if the virus is ineffective for some reason [4], some of the Cas proteins recruit pieces of viral DNA and integrate these "spacers" into an array separated by palindromic repeated sequences in the CRIPSR locus of the bacte-rial genome.…”
Section: Introductionmentioning
confidence: 99%
“…The CRISPR-Cas mechanism for immunity has three stages (2,3). Following a first encounter with a virus, after a successful defense through another mechanism or if the virus is ineffective for some reason (4), some of the Cas proteins recruit pieces of viral DNA and integrate these spacers into an array separated by palindromic repeated sequences in one of several CRISPR loci (5) of the bacterial genome.…”
mentioning
confidence: 99%
“…A clue may be offered in the fact that older spacers often correspond to evolutionarily conserved regions in the genomes of persistent viruses (3,11,(20)(21)(22). In fact, even if an older spacer is not a perfect match to a new invader, it may efficiently prime the acquisition of new immunity (23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Reprinted from ref. 13, which is licensed under CC BY 3.0. spacers due to the selective pressure for targeting dominant phage genotypes (14), as had been observed in studies of environmental strains. A population dynamics model showed that a less diverse CRISPR spacer distribution that is focused on the most effective spacers evolved when phage had multiple protospacers that differ in their effectiveness, although a diverse spacer locus evolved when phage protospacers differed in their ease of acquisition (15).…”
mentioning
confidence: 99%
“…Conversely, if the size is above the optimal value, there are so many distinct potential spacers that the requirement of d c Cas/crRNA complexes per phage type is not able to be met. This penalty addresses the biochemical requirement for efficient use and low energy consumption of Cas proteins (13).…”
mentioning
confidence: 99%